PAI TeacherÃ¢â¬â¢s Role in Optimizing Competency Based Curriculum Implementation - Zainuddin, Mohammad Riza (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2017)
The curriculum is an important thing in the world of education, without an educational curriculum will run unbalanced. Competency-based curriculum is an effort in improving the quality of education quality, this is what causes a problem and adjustment of PAI Teachers in teaching and learning process. in the application of Curriculum-Based Competence Islamic Religion Teachers are always preparing in advance to be given to students, be it related to the syllabus, learning tools, media, material mastery, notebook (personal) even performent a Master is also important, in addition to Master always use various methods learning which is interspersed with fun things to be unsaturated, all efforts to maximize the application of Competency Based Curriculum conducted by Islamic Religious Education Teachers so that students are more independent and not dependent on Teachers, and students are more creative looking for problem solving or material materials that exist out of school. The existence of the optimal application is done by Islamic Religious Education Teachers by seeking various preparations, methods and other efforts as mentioned above, as well as cooperation among teachers, both Islamic Religious Education Teachers and Counseling Guidance and general teachers. Therefore, efforts are made more on the increase again that the madrasah especially Islamic Religious Education Teachers improve again its cooperation with parents and more students execute themselves with other teachers, especially Teacher Counseling to monitor the problems and development of students.